Suitability of CO2 capture technologies for carbon capture and storage in India. Issue 4 (8th January 2016) - Yadav, Dharmender; Chandel, Munish K.; Kumar, Pramod
Abstract: The Indian power sector relies heavily on coal power plants for electricity generation as 59% of the total installed capacity is from coal power plants. Considerable research has been done in developed countries to analyze the suitability of CO2 capture technologies for coal power plants, but not in India. This work analyzes the suitability of various CO2 capture technologies for Indian coal power plants on the basis of different parameters: energy penalty, cost of CO2 capture, efficiency, and age and size of the power plant. An Integrated Environmental Control Model (IECM) was used to simulate the power plants, and to calculate the energy penalty and cost of capture. All existing 517 units of 115 coal power plants in India, along with one Integrated Gasification Combined Cycle (IGCC) plant and one ultra‐supercritical plant were analyzed for CO2 capture suitability. Results show that the total installed capacity of Indian coal power plants would reduce to somewhere between 66 896 and 105 991 MW, depending on the CO2 capture technology applied, from and existing 126 320 MW. The average efficiency of Indian coal power plants would reduce from the current 29% to 24.4%, 20.7%, and 15.4% if we retrofit the plants with amine‐, ammonia‐, and membrane‐based capture systems, respectively. Cost of CO2 capture for these three technologies would be $42.3, $75.2, and $81.9 per tonne of CO2, respectively. The CO2 capture technologies would be better off on coal power plants which are less than 20 years old, as the energy penalty would be less. © 2015 Society of Chemical Industry and John Wiley & Sons, Ltd